Evolución histórica de los créditos y depósitos de las cajas municipales en la región Loreto, período 2013 – 2022 - Flores Guerrero, Luis Alejandro (2024)
The general objective of this research was: Analyze the historical evolution of credits and deposits of municipal boxes in the Loreto region during the period 2013 to 2022. For this, the following method was used: the type of research was quantitative, non-experimental design since it was carried out without the deliberate manipulation of variables, it was longitudinal in design, and descriptive in scope. The results demonstrate the growing historical evolution of direct credits, from 2013 to 2022, registering in January 2013: S/ 206,574.00 soles and reaching S/ 432,102.00 soles in December 2022. Monthly time deposits showed slow growth from 2013 to 2022 constantly, registering in January 2013: S/ 135,244.00 soles and reaching December 2022 with S/ 181,962.00 soles. While monthly savings deposits grew unevenly with a notable decrease in 2020 as a result of the pandemic where no data was recorded until December of that year, registering in January 2013: S/ 34,944.00 soles and reaching December 2013. 2022 with S/ 72,135.00 soles. Likewise, it is concluded by accepting the general hypothesis, stating that: The historical evolution of credits and deposits from municipal boxes is increasing in the Loreto region during the period 2013 to 2022, because direct loans grew by 86.81%. Time deposits register a growth of 29.88%. Finally, savings deposits showed a growth of 103.06%.